Focused hydrocarbon‐migration in shallow sediments of a pockmark cluster in the Niger Delta (Off Nigeria). (19th January 2017) - de Prunelé, Alexis; Ruffine, Livio; Riboulot, Vincent; Peters, Carl A.; Croguennec, Claire; Guyader, Vivien; Pape, Thomas; Bollinger, Claire; Bayon, Germain; Caprais, Jean‐Claude; Germain, Yoan; Donval, Jean‐Pierre; et al.
Abstract: The Niger Delta is one of the largest hydrocarbon basin offshore Africa and it is well known for the presence of active pockmarks on the seabed. During the Guineco‐MeBo cruise in 2011, long cores were taken from a pockmark cluster in order to investigate the state of its current activity. Gas hydrates, oil, and pore‐water were sampled for geochemical studies. The resulting dataset combined with seismic data reveal that shallow hydrocarbon migration in the upper sedimentary section was focused exclusively within the pockmarks. There is a clear tendency for gas migration within the hydrate‐bearing pockmarks, and oil migration within the carbonate‐rich one. This trend is interpreted as a consequence of hydrate dissolution followed by carbonate precipitation in the course of the evolution of these pockmarks. We also demonstrate that Anaerobic Oxidation of Methane (AOM) is the main process responsible for the depletion of pore‐water sulfate, with depths of the Sulfate‐Methane Transition Zone (SMTZ) ranging between 1.8 and 33.4 m. In addition, a numerical transport‐reaction model was used to estimate the age of hydrate‐layer formation from the present‐day sulfate profiles. The results show that the sampled hydrate‐layers were formed between 21 and 3750 years before present. Overall, this work shows the importance of fluid flow on the dynamics of pockmarks, and the investigated cluster offers new opportunities for future cross‐site comparison studies. Our results imply that sudden discharges of gas can create hydrate layers within the upper sedimentary column which can affect the seafloor morphology over few decades. Key Points: Seismic surveys and geochemical analyses were combined to study a cluster of hydrate‐bearing pockmarks The pockmark dynamics is governed by fluid flow Sulfate‐profile simulation allowed estimating the formation age of four selected hydrate layers